2009
DOI: 10.1186/1472-6920-9-75
|View full text |Cite
|
Sign up to set email alerts
|

A survey of attitudes toward clinical research among physicians at Kyoto University Hospital

Abstract: BackgroundIn Japan, only clinical research related to investigational new drug trials must be notified to regulatory bodies, and this lack of a uniform standard for clinical research has caused a number of difficulties. The objective of this study was to assess the willingness of physicians to participate in clinical research and to identify effective methods to promote and enhance clinical research.MethodsWe conducted a cross-sectional survey by administrating questionnaires to physicians in 31 departments in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 8 publications
7
53
0
Order By: Relevance
“…The barriers that physicians usually encounter in conducting clinical research are highlighted in many studies 13,16,21,22. Fayter et al13,18 identified these barriers as system-, organization-, research-, and physician-related.…”
Section: Barriers To Participation In Clinical Researchmentioning
confidence: 99%
“…The barriers that physicians usually encounter in conducting clinical research are highlighted in many studies 13,16,21,22. Fayter et al13,18 identified these barriers as system-, organization-, research-, and physician-related.…”
Section: Barriers To Participation In Clinical Researchmentioning
confidence: 99%
“…This problem has been identified in studies 4,22–24 concerning clinical trials in human medicine as well. For example, a study 13 involving pediatricians revealed that spending more time in the initial interview or discussion with potential clinical trial participants led to lower refusal rates, which is a strategy that is not always feasible in busy general practices.…”
Section: Discussionmentioning
confidence: 99%
“…Survey results from Kyoto University Hospital indicate that Japanese physicians seek greater knowledge of clinical research design and biostatistical concepts 6. In Japan, only a few institutes offer formal clinical research training including Kyoto University, University of Tokyo, Keio University, and St. Luke's International Hospital.…”
mentioning
confidence: 99%